Dynamics of the Double Burden of Malnutrition and the Changing Nutrition Reality - Popkin, Barry M. (2020)
Barry Popkin POLICY SEMINAR Virtual Event - The New Nutrition Reality: Time to Recognize and Tackle the Double Burden of Malnutrition! DEC 1, 2020 - 09:30 AM TO 11:15 AM EST